Land Use Changes of Paddy Fields in Karangmalang Subdistrict, Sragen Regency in 2014 and 2024 - Muh. Husyain Rifai (International Journal of Science and Environment (IJSE), 2025)
Population growth has led to an increased demand for housing needs and public facilities, ultimately placing pressure on land availability. This condition causes some agricultural land to convert into non-agricultural land. This study aims to determine the changes of paddy fields that occurred in Karangmalang Subdistrict, Sragen Regency in 2014 and 2024. To obtain image data, the researchers used image interpretation and digitalization techniques on Landsat 8 images in 2014 and Sentinel-2 L2A images in 2024, followed by an overlay process on the 2014 and 2024 land use maps to determine changes in the use of paddy fields in Karangmalang Subdistrict in 2014 & 2024. The results of this study found that the use of paddy fields in Karangmalang Subdistrict between 2014 to 2024 showed a decrease in area from 2964.19 ha to 2864.08 ha, or a decrease of about 100.10 ha.